Asymmetric ENSO Forcing on the South Pacific Meridional Mode - Cheng Qi; Fan Jia (Geophysical Research Letters)
Abstract The South Pacific Meridional Mode (SPMM) influences El Niño‐Southern Oscillation (ENSO) variability, but whether ENSO triggers SPMM remains unclear. We show that ENSO can induce an in‐phase SPMM event via atmospheric teleconnections, beginning in early boreal summer of the ENSO‐developing year, with a negative asymmetry. Strong La Niña induces negative SPMM more effectively than El Niño induces positive SPMM, due to differences in ENSO teleconnections and their intensity. During boreal summer and fall of strong La Niña, intense transient eddy feedback reshapes the Pacific‐South America pattern into a South Pacific Oscillation‐like pressure dipole, strengthening trade winds and promoting negative SPMM growth, a process absent in El Niño. In boreal winter, stronger La Niña teleconnections sustain negative SPMM into spring. Half of the negative SPMM events co‐occur with negative North Pacific Meridional Mode, contributing to multi‐year La Niña development. These findings advance the understanding of SPMM and its impact on ENSO.